Mandela's way : fifteen lessons on life, love, and courage - Stengel, Richard (New York : Crown Publishers, 2009)
We long for heroes and have too few. Nelson Mandela, who recently celebrated his ninety-first birthday, is the closest thing the world has to a secular saint. He liberated a country from a system of violent prejudice and helped unite oppressor and oppressed in a way that had never been done before. Now Richard Stengel, the editor of Time magazine, has distilled countless hours of intimate conversation with Mandela into fifteen essential life lessons. For nearly three years, including the critical period when Mandela moved South Africa toward the first democratic elections in its history, Stengel collaborated with Mandela on his autobiography and traveled with him everywhere. Eating with him, watching him campaign, hearing him think out loud, Stengel came to know all the different sides of this complex man and became a cherished friend and colleague.
Courage is not the absence of fear -- Be measured -- Lead from the front -- Look the part -- Lead from the back -- See the good in others -- Keep your rivals close -- Have a core principle -- Know when to say no -- Know your enemy -- It's always both -- Love makes the difference -- It's a long game -- Quitting is leading too -- Find your own garden -- The chain of leadership.
Keywords: Mandela, Nelson, -- 1918-; Conduct of life; Courage; Leadership